Immune tolerance of allogeneic haematopoietic cell transplantation supports donor epidermal grafting of recessive dystrophic epidermolysis bullosa chronic wounds. (1st June 2021) - Ebens, C.L.; McGrath, J.A.; Riedl, J.A.; Keith, A.R.; Lilja, G.; Rusch, S.; Keene, D.R.; Tufa, S.F.; Riddle, M.J.; Shanley, R.; Van Heest, A.E.; Tolar, J.
Summary: Background: Chronic wounds, a common morbidity in recessive dystrophic epidermolysis bullosa (RDEB), lack definitive therapies. Objectives: To assess allogeneic epidermal skin grafts in terms of wound healing and durability over time. Methods: In a prospective, open‐label clinical trial for postallogeneic haematopoietic cell transplantation (post‐alloHCT) patients with RDEB, up to nine chronic wounds per patient were grafted over 1 year. Epidermal grafts measuring 5 cm 2 were obtained from related alloHCT donors in the outpatient setting using the CELLUTOME TM Epidermal Harvesting System. Wounds were photographed and symptom inventories completed at baseline and 6, 12 and 52 weeks after grafting. The trial was registered at ClinicalTrials.gov (NCT02670837). Results: Between August 2016 and January 2019, eight patients with RDEB received a total of 35 epidermal allografts at a median of 1157 days (range 548–2884) post‐alloHCT. The median (interquartile range) percentage reductions in wound surface area were 75% (52–94), 95% (72–100) and 100% (97–100) at 6, 12 and 52 weeks postgraft, respectively, each significantly reduced from baseline ( P < 0·001). Donor harvest sites healed quickly without scarring. Biopsy evaluation at 1 year of an epidermal allograft site revealed wildtype type VII collagen (immunofluorescence), anchoring fibrils (electron microscopy), and full‐thickness skin whole‐DNA donor chimerism of 42% (compared with 16% in concurrently biopsied native skin). This strategy subsequently supported release of RDEB pseudosyndactyly. Conclusions: The immune tolerance established by alloHCT supports successful adoptive transfer of donor epidermal grafts. Persistence of donor grafts in a single patient beyond 1 year and observed migration of donor‐grafted cells into adjacent wound suggest that epidermal allografts include nonterminally differentiated cells and/or trigger recruitment of donor bone‐marrow‐derived cells to mediate wound healing.